REAKTUALISASI EPISTEMOLOGI “BONDO BAHU PIKIR”: STUDI KOMPARATIF ETOS KERJA MAHASISWI-GURU PESANTREN AL IMAN PUTRI PONOROGO - Ishaqi Maulina; Muhammad Galih Rakasiwi (Pascasarjana Universitas Al-Qolam Malang, 2026)
In the era of disruption, the rise of pragmatism and materialist mindsets has significantly shifted youth orientations toward transactional careers. Conversely, Islamic boarding schools (pesantren) consistently maintain an alternative microcosm rooted in total devotion. This study aims to explore the reactualization of the local philosophy